Cyber Espionage in Indonesia: Legal Challenges and The Role of Institutions in the Digital Era - Daryanto, Eko; Riyanta, Stanislaus; Hanita, Margaretha; Munabari, Fahlesa (Deviance Jurnal Kriminologi, 2024)
In this digital era, cyber espionage is a serious threat to countries around the world, including Indonesia. This study looks at the legal framework governing cyber espionage, and the challenges and opportunities for law enforcement it faces as well as its development. Through a qualitative methodology based on institutional theory, this study reveals that the existing legal framework, particularly The Electronic Information and Transactions Law (ITE Law) and Penal Code (KUHP), is still not sufficient. Lack of legal clarity and inconsistencies — both internationally and nationally — make things even more difficult. Other contributing factors to poor law enforcement include limited institutional capacity resulting in the lack of well-trained human resources, insufficient technological infrastructure, and inter-agency collaboration. The process of isomorphism, which is understood in institutional framework as imitation of best practices implemented by other countries to cope with cyber espionage, does not always work because each country has different contexts and needs. This study shows that most literature in cyber espionage underscores the need for comprehensive legal reform, improvement of institutional capacity, quality of cooperation, and better understanding of the role of non-state actors in building an effective cyber security system in Indonesia.